Japan : An Economic Survey 1953 - 1973 - Boltho, Andrea (London : Oxford university Press, 1975)
The book contains a summary description of the pace and pattern of economic growth in the period covered; and it outlines the main economic problems confronting government in the country, the objectives of economic policy and the chosen means of economic management.
includes index
occ 16/01/2019
Loans
Keywords: Economic history; Japan